"He was Drugged up on Something..." Portrayals of Drugs and Violence on Crime Scene Investigation (CSI) as System Justification. (October 2021) - Sohoni, Tracy; Snell, Julie; Harden, Elizabeth
We conducted a content analysis of the first two and last two seasons of the popular crime drama Crime Scene Investigation ( CSI ), to determine the extent to which depictions of the intersection of substance use and violence were consistent with research. Using the lens of system justification theory, we find that CSI focuses on aspects of crime that preserve the status quo, specifically it overemphasizes the negative impact of illicit substances as opposed to legal substances (such as alcohol), and it emphasizes the psychopharmacological role of drugs in violent crime compared to systemic violence related to the illegality of drug markets, even though research demonstrates that systemic violence makes up a large proportion of substance-related homicides. Despite significant changes in drug policy that occurred during the time that CSI was on the air, we find these portrayals are largely unchanged between episodes that were broadcast between 2000–2002 versus those that aired 2014–2015.